Kihívások és reformok az egészségügyben - Domján, Péter; Turcsányi, Katalin (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The health system is one of greatest distributive system and it is branch of public sector, which is fought a lot of phenomena of enonomic crisis. Steps, which correctly converge to trend of European is significantly dependent on efficient co-operation in the system of modernisation. The bese of co-operation are work and risk share method. The mainly question, how can stop or decrease of cost rising and increse efficiency without lose the level of standard and at same time we are operating high level health system. A lot of people deem the health as duty of the state and wait the increase of health's efficiency and the better quality and financing from private sector, which is more and more participated. The study is rewied the funciton of private sector in the health and the scope of the expectation